الأطر النظرية والمفاهيمية للسياحة - مباركة، عثمان (جامعة عاشور زيان الجلفة, 2019)
تعتبر السياحة أحد أكبر وأهم الظواهر الاقتصادية والاجتماعية في عالم اليوم، فبعد أن كانت السياحة نشاطاً يقتصر على فئة قليلة من الأثرياء في مستهل القرن العشرين أصبحت ظاهرة جماهيرية خاصة في الدول الأكثر نمواً بحلول السبعينيات، حتى أنها أصبحت في متناول فئات أكبر من الناس في معظم بلدان العالم وهذا راجع إلى تحسن ظروف المعيشة، وتطور وسائل النقل وظهور الحاجة إلى الراحة والترفيه أثناء العطل والإجازات. وسنركز في هذه الورقة البحثية على أهم المفاهيم السياحية، انطلاقاً من المراحل المختلفة التي مرت بها السياحة منذ العصور القديمة إلى غاية المرحلة الحالية، وكذلك أهم أنواع السياحة، بالإضافة إلى النظريات المفسرة لها. Tourism is considered to be one of the largest and most important economic and social sectors in today's world. After a small group of wealthy people used to monopolize it at the beginning of the 20th century, tourism became a mass affair in the most developed countries by the 1970s because it became accessible to larger groups due to: the improvement of living conditions, the evolution of transportation and the emergence of the need for rest and recreation during holidays and vacations. Thus, this paper is going to focus on the most important concepts related to tourism, as it will deal with the various stages that it has passed through, from ancient times till the current stage. As well as, the most important types of tourism, in addition to the different theories related to it.
Keywords: التنمية الاقتصادية -- قطاع السياحة -- التنمية الاجتماعية -- وزارة السياحة